DANCE WORK "SHADOW" AS AN EXPRESSION OF SELF-DISCOVERY IN DRAMATIC DANCE FORM - Geraldo, Muhammad Trio; Sasanadjati, M.Hum, Dra. Jajuk Dwi (Solah, 2024)
Shadow Dance is a dance work that departs from the phenomenon of multi-talent. There are two focuses in Shadow dance work, namely the focus of content about a search for human identity from the many talents he has and the focus of the form presented in dramatic form. The writing of the Shadow dance work applies the Construction Method I in Jacqueline Smith’s Theory. The purpose of writing this dance work is to reveal the search for human identity from the many multi-talents it has and describe the dramatic dance form. The result of a content disclosure in the Shadow dance work analogizes the talent as a shadow expressed through a light property and simple fashion makeup, a proscenium stage complete with lighting that is used to build a change of atmosphere in each scene. Musical accompaniment becomes a supporter in Shadow dance work then forms a double cone dramatic design. Shadow dance work has the theme of self-discovery. The contemporary dance form with a dramatic dance type becomes the author’s medium to convey messages to the audience by bringing up a symbol and a dramatization in each scene through expressions, movements, vocals, and the interaction of dancers with dancers and dancers with the audience.